PENGEMBANGAN MODUL MENULIS SURAT BISNIS BAHASA INGGRIS UNTUK KELAS XII SEKOLAH MENENGAH KEJURUAN - Diselita, Susi -; -, Rachmawati -; -, Saharudin - (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2011)
This research is aimed at developing a module of writing business letters in English for  twelfth grader of  vocational  school. The module is developed by using  Dick’s et al. (2005) development model. This research  used only 9 com-ponents of the model. In the vocational school module is one important alternatives for delivering  material  to the students. Validation of the module are conducted by the experts (material and media), an English teacher, and the students. The validation result from the  experts   state that the module is good, according to the contents of the module is applicable for the students, the technique of writing of the module is good, and language composing is good. The English  teacher,  as the  user of the product, states that this module is  clear, interesting, appropriate, effective and easy to use. From the one-to-one evaluation, small group evaluation, field trial, the attitude questionnaires, interviews and observations indicate that the module is good, interesting and appropriate for them. It can be concluded that the module can be used in learning English in twelfth grader of vocational school. Keywords: module, business writing, development model